Irrigation water resource management for sustainable agriculture - The Ankobra Basin, Ghana - Yidana, S.M.; Ophori, D.; Banoeng-Yakubo, B. (Journal of Irrigation and Drainage Engineering, 2007)
Two irrigation water assessment methods, the USDA classification scheme and the soil infiltration potential, were applied to water from three different locations (Ankwaso, Dominase, and Prestea) of the Ankobra River basin in Ghana, to evaluate its effectiveness as a sustainable water resource for irrigation. The study classifies water from all three locations into the low salinity, low sodicity zone with Prestea and Ankwaso having waters of the highest sodicity and salinity, respectively. A classification scheme based on effects of the water on the hydraulic properties of soils reveals that water from all locations of the basin has the potential to affect the infiltration properties of soils, especially when applied over a long period of time. Linear regression analysis indicates a strong relationship between electrical conductivity (EC) and sodium adsorption ratio (SAR) at R2 = 0.773 (n=30) for Prestea. This relationship is probably due to the fact that Na, Mg, and Ca, which are the major determinants of water SAR, are also the major contributors to the water EC at Prestea, and this is probably due to surface mining activities, which encourage the weathering of calcic and albitic feldspars. Time series analysis reveals that EC and SAR for Dominase and Prestea, respectively, have increased from 1989 to 1992. On the other hand, SAR and EC have been decreasing since 1989, for the two locations. Forecast data from the time series analyses agree well with observed data, at 0.01 level of significance. Projections were made at ten time steps ahead of 1992 using time series analysis. © 2007 ASCE.
Keywords: Adsorption; Electrical conductivity; Ghana; Hydraulic conductivity; River basin; Sodium